2003
DOI: 10.1093/annonc/mdg029
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly high-dose gemcitabine alone or in combination with capecitabine in patients with metastatic pancreatic adenocarcinoma: a randomized phase II trial

Abstract: Results of this trial suggest a fairly good therapeutic index for the combination of biweekly high-dose gemcitabine and capecitabine for the treatment of advanced pancreatic cancer. Despite a somewhat superior clinical benefit response rate, no advantage over single-agent gemcitabine, however, was noted in terms of objective efficacy parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(95 citation statements)
references
References 23 publications
2
92
0
1
Order By: Relevance
“…Nineteen studies involving 4697 patients were included (Supplementary Table 2) (Berlin et al, 2002;Colucci et al, 2002;Wang et al, 2002;Heinemann et al, 2003;Scheithauer et al, 2003;Li and Chao, 2004;Ohkawa, 2004;Rocha Lima et al, 2004;Viret et al, 2004;Cunningham et al, 2005 Cullinan 1990 Cullinan 1990 Cullinan 1990 …”
Section: Gemcitabine Vs Gemcitabine-based Combination Chemotherapymentioning
confidence: 99%
“…Nineteen studies involving 4697 patients were included (Supplementary Table 2) (Berlin et al, 2002;Colucci et al, 2002;Wang et al, 2002;Heinemann et al, 2003;Scheithauer et al, 2003;Li and Chao, 2004;Ohkawa, 2004;Rocha Lima et al, 2004;Viret et al, 2004;Cunningham et al, 2005 Cullinan 1990 Cullinan 1990 Cullinan 1990 …”
Section: Gemcitabine Vs Gemcitabine-based Combination Chemotherapymentioning
confidence: 99%
“…The combination of gemcitabine and 5-fluoro-2 0 -deoxyuridine (an intermediate metabolite of capecitabine) has demonstrated synergistic activity in vitro (Ren et al, 1998). Several phase I trials have evaluated combinations of gemcitabine and capecitabine, and have shown that full single-agent doses can be delivered in combination (Schilsky et al, 2002;Hess et al, 2003;Scheithauer et al, 2003). This single institution phase II trial aimed to evaluate the activity and toxicity of a combination of gemcitabine and capecitabine in patients with metastatic renal cancer refractory to or unsuitable for immunotherapy.…”
mentioning
confidence: 99%
“…Recent studies on erlotinib, an epidermal growth factor receptor inhibitor, plus gemcitabine, provided the foundation for approval of such regimens for the treatment of advanced pancreatic adenocarcinoma (24) and reported a SDR of 53-59.3% (25,26). The most frequently reported treatment-related toxicities of gemcitabine, alone or in combination with other drugs, are leukopenia, thrombocytopenia and neutropenia (26,27).…”
Section: Discussionmentioning
confidence: 99%